2017
DOI: 10.18632/oncotarget.15222
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine and paracrine STIP1 signaling promote osteolytic bone metastasis in renal cell carcinoma

Abstract: Bone metastases are responsible for some of the most devastating complications of renal cell carcinoma (RCC). However, pro-metastatic factors leading to the highly osteolytic characteristics of RCC bone metastasis have barely been explored. We previously developed novel bone-seeking RCC cell lines by the in vivo selection strategy and performed a comparative proteome analysis on their total cell lysate. Here, we focused on STIP1 (stress-induced phosphoprotein 1), the high up-regulated protein in the bone-seeki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…2a, b). Our previous results indicated that rhHOP promoted hepatocellular carcinoma cell (HCC) proliferation [25], and it was reported that rhHOP increased ovarian cancer cell viability [24] and renal cell cancer metastasis [26]. Thus, we determined the effects of HOP on GC cell growth.…”
Section: Exogenous Hop Signaling Promoted Cell Proliferation In Gc Cementioning
confidence: 96%
“…2a, b). Our previous results indicated that rhHOP promoted hepatocellular carcinoma cell (HCC) proliferation [25], and it was reported that rhHOP increased ovarian cancer cell viability [24] and renal cell cancer metastasis [26]. Thus, we determined the effects of HOP on GC cell growth.…”
Section: Exogenous Hop Signaling Promoted Cell Proliferation In Gc Cementioning
confidence: 96%
“…Knockout mice lacking STIP1 are embryonic lethal, suggesting a key developmental role for this molecule 6 . Growing evidence also indicates that STIP1 is markedly overexpressed in various human solid malignancies 7 – 13 . Conversely, its repression blocks both tumor cell proliferation 11 and migration 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with metastatic RCC (mRCC) of other organs represent an unfavorable subset of individuals. Especially the occurrence of the bone metastasis is widely accepted as a significant prognostic factor of life expectancy of patients [3] .…”
Section: Introductionmentioning
confidence: 99%